Examining land reform in South Africa: evidence from survey data - Ryan, Joanna (School of Economics, 2018)
Land and land reform have long been contentious and highly charged topics in South Africa, with land performing the dual functions of redress for the past and development for the future. This research explores both these aspects of land, with the focus being on the impact of land receipt on household welfare and food insecurity, and social preferences for fairness and redistribution more generally. One of the main aims is to contribute to the land reform debate by providing previously-lacking quantitative evidence on the aggregate welfare outcomes of land redistribution, as well as the extent of social preferences for redistribution in the land restitution framework. In exploring these issues, the welfare outcomes of land are first explored using the National Income Dynamics Study (NIDS) data and unconditional quantile regression analysis. The focus is then narrowed to the food insecurity impact of land receipt, beginning with a methodological chapter outlining the development of a new food insecurity index applying the Alkire-Foster method of multidimensional poverty measurement (2009; 2011). This is followed by the presentation and discussion of food insecurity profiles of land beneficiary and non-beneficiary households. The new index is also used as an outcome measure in exploring the determinants of household food insecurity. These two sections again use the NIDS data. The final section shifts the emphasis from the economic welfare benefits of land redistribution to notions of fairness and social justice encapsulated by land restitution. A behavioural laboratory experiment is used to investigate social preferences for fairness, and the factors that influence redistributive inclinations, by exploring the relative weights placed on fairness considerations and self-interest, as well as the fairness ideal. The findings indicate that beneficiaries do not use the land received for productive purposes, a possible explanation for the limited economic welfare impacts of land reform that are observed. Despite this limited developmental impact, the laboratory experiment makes it clear that land reform plays an important role in addressing other needs and wants in society, particularly in respect of preferences for fairness and addressing historical injustices.